Gen-Next Entrepreneur : Passion, Efficacy, Intention, and the Role of Family - Kar, Brajaballav; Tripathy, Sugato (AMC Indian Journal of Entrepreneurship, 2020)
The role of the family or community in entrepreneurship is well acknowledged. At the first level, it can act as the role model, provide experiential learning opportunity, help in the ideation process, and often provides resources for entrepreneurial venture. Family tradition in India is expected to bolster entrepreneurial efforts of the second generation, specifically if the family members are already into business. The joint family tradition, accounting, and early entry into business are some of the well-known features of the business community. This study deals with a contrarian case. The business, family members, and process operate as a system in a specific context. The decision outcome may not always favour the entrepreneurial ambition of a next-generation individual. The entrepreneur had to disengage from the establishment, and create his own venture. The desire for inclusion, independence, and entrepreneurial efficacy are the hallmarks of this case study. It presents the sequence of events, dynamics, and challenges of a next generation entrepreneur from a business family. It also briefly discusses various aspects of the heavy machinery and precision making tools sector in India. The case study supporting resources are given to facilitate case discussion with the participants.